2023
DOI: 10.1088/1755-1315/1135/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Removal of pollutants from wastewater using activated carbon from durian peel

Abstract: The efforts in reducing food waste can lead to better water management with less land required for food production and indirectly having a positive impact on the livelihoods and the environment. In order to support the practice of reducing food waste in Brunei Darussalam, one must find ways to recycle or reuse them, particularly waste generated from fruit peels. This paper investigates the feasibility of utilising Durian (Durio zibethinus) rinds to remove pollutants in wastewater, namely Chemical Oxygen Demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Durian peel can be used to remove pollutants from wastewater by the process of adsorption. A study found that carbonised durian peel can remove up to 68.2% of Chemical Oxygen Demand (COD) in wastewater [27]. Durian peel extract can be used as an antibacterial agent in food products.…”
Section: Durian Peelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Durian peel can be used to remove pollutants from wastewater by the process of adsorption. A study found that carbonised durian peel can remove up to 68.2% of Chemical Oxygen Demand (COD) in wastewater [27]. Durian peel extract can be used as an antibacterial agent in food products.…”
Section: Durian Peelsmentioning
confidence: 99%
“…Durian peel extract can be used as an antibacterial agent in food products. A study found that sterilized durian-rind pectin showed strong antibacterial activity towards Staphylococcus aureus and Escherichia coli [27]. Durian peel extract can be used as an antimicrobial agent in food products.…”
Section: Durian Peelsmentioning
confidence: 99%
“…Utilizing LB to produce carbon materials is a viable choice due to the high carbon content present in lignin. Various sources of LB, such as durian shells [ 91 , 92 ], coconut shells [ 93 , 94 , 95 ], and food waste [ 96 ], have been effectively used to prepare activated carbon with high adsorption properties, based on different advantages of carbonization and activation methods. LBC finds wide applications in the industrial and residential sectors ( Figure 10 ).…”
Section: Applications Of Lignocellulosic Biomass-derived Biocharmentioning
confidence: 99%